Back Cover: Enzyme‐like Supramolecular Iridium Catalysis Enabling C−H Bond Borylation of Pyridines with meta‐Selectivity (Angew. Chem. Int. Ed. 33/2021). Issue 33 (21st June 2021) - Trouvé, Jonathan; Zardi, Paolo; Al‐Shehimy, Shaymaa; Roisnel, Thierry; Gramage‐Doria, Rafael
Abstract : Like an enzyme best describes the supramolecular catalyst reported by Rafael Gramage‐Doria et al. in their Research Article on page 18006 . The remotely located Zn⋅⋅⋅N interactions within an iridium borylating catalyst are responsible for the unique selectivity and reactivity patterns observed for pyridine C−H bond functionalization. The pyridine approaches the substrate recognition pocket like a Perseid shooting star. Artwork: Romain Baloche.